Variation d’expression des symptômes et de l'infectiosité de la maladie de bunchy top chez des cultivars de bananier - Chabi, Modeste; Gbèblonoudo Dassou, Anicet; Adoukonou-Sagbadja, Hubert; Omondi, Bonaventure Aman Oduor (2022)
Consistent detection of the banana bunchy top disease is important for its management. This study assessed the cultivar differences between cultivars and